2013
DOI: 10.1007/978-3-642-39206-1_25
|View full text |Cite
|
Sign up to set email alerts
|

On Randomized Online Labeling with Polynomially Many Labels

Abstract: Abstract. We prove an optimal lower bound on the complexity of randomized algorithms for the online labeling problem with polynomially many labels. All previous work on this problem (both upper and lower bounds) only applied to deterministic algorithms, so this is the first paper addressing the (im)possibility of faster randomized algorithms. Our lower bound Ω(n log(n)) matches the complexity of a known deterministic algorithm for this setting of parameters so it is asymptotically optimal. In the online labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A surprising aspect of our results is how they contrast with the polynomial regime m = n 1+Θ (1) where randomized and deterministic algorithms are asymptotically equivalent [6,7,23]. Our final upper-bound result considers a continuum between these regimes, where m = ω(n) ∩ n o (1) .…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…A surprising aspect of our results is how they contrast with the polynomial regime m = n 1+Θ (1) where randomized and deterministic algorithms are asymptotically equivalent [6,7,23]. Our final upper-bound result considers a continuum between these regimes, where m = ω(n) ∩ n o (1) .…”
Section: Introductionmentioning
confidence: 87%
“…In the polynomial regime, when m n = n Θ (1) , the amortized cost becomes O(log n) [2,33,43]. These bounds are known to be tight for both deterministic and randomized algorithms [6,7,23].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…All of the work mentioned so far (both upper and lower bounds) is for the case of deterministic algorithms. In work subsequent to this paper, a subset of the authors [5] showed that the Ω(n log n) lower bound for the case m = n 1+C of polynomially many labels extends for randomized algorithms. The results in that paper do not subsume this one because (a) The lower bounds for randomized algorithms don't extend to the range that m is superpolynomial in n (as do the results here) and (b) The lower bound proofs here are conceptually simpler.…”
Section: Introductionmentioning
confidence: 96%